转录因子T-bet在外周T细胞淋巴瘤患者中的表达及其预后意义初探 (Zhonghua Xue Ye Xue Za Zhi, 2016)
OBJECTIVE: To evaluate the expression of transcription factor T-bet (T-box expressed in T cells) and explore its effects on prognosis in peripheral T-cell lymphoma (PTCL). METHODS: This study included 109 previously untreated patients diagnosed with PTCL in the pathology system at Peking Union Medical College Hospital from 2007 to 2013. Formalin-fixed, paraffin-embedded blocks and clinical information of these patients were collected. T-bet expression was examined by immunohistochemical stain, while its relationship with clinical feature and prognosis was analyzed. RESULTS: 109 PTCL patients included 60 PTCL-not other specified (PTCL-NOS) cases and 18 NK/T-cell lymphoma. The positive rate of T-bet was 42.2% overall, 43.3% in PTCL-NOS and 44.4% in NK/T lymphoma. T-bet high expression wasn't correlated with OS in PTCL patients (P=0.586) by Kaplan-Meier analysis. Further stratification by pathological subgroup implied a correlation of T-bet high expression with better survival in NK/T lymphoma (P=0.004), but not in PTCL-NOS (P=0.309). Multivariate analysis confirmed that high ECOG score (≥2) was an independent predictor of overall survival (HR=5.907, 95%CI 2.399~14.549, P<0.001). CONCLUSION: T-bet was detected in several PTCL subgroups with diversities, which is positively correlated with overall survival in NK/T-cell lymphoma.